Some key technical issues in the evolution from cloud network to computing network - Chang CAO; Shuai ZHANG; Ying LIU; Xiongyan TANG (Dianxin kexue)
Firstly, the development trend of cloud-network integration technology in recent years, the new problems and challenges it faces were analyzed.Then, based on the heterogeneous computing power, the sinking of computing power, and the new changes in computing-network linkage in business development, six major computing and network capabilities were proposed.Convergence requirements, combined with multi-cloud connection, differentiated bearer, and hierarchical security, discussed the case of building new capabilities and new business experience around the computing network.The analysis results show that it can be concluded that the computing network and the cloud network are closely related in the technical system, and the integration of the computing network is the inevitable result of the development and evolution of the integration of the cloud and the network, and it is also an inevitable choice for the development of the digital economy.